Import dependency of food production - Knuuttila, Marja; Vatanen, Eero; Niemi, Jyrki; Jansik, Csaba (European Association of Agricultural Economists (EAAE), 2014)
Self-sufficiency figures based on the relationship between domestic production and consumption fail to take into account the fact that domestic production itself is dependent on imported resources. In this paper, an indicator for measuring the import content of food production industries is introduced. With the aid of Eurostat input–output tables, the total dependency on imports, comprising both direct as well as indirect imports of raw materials and intermediates, is calculated for Finland, Germany and Denmark. The results of agricultural and food manufacturing production are presented, indicating a growing trend in import dependency, including energy, chemicals, feed protein and services.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; tuontipanos; tuotosmalli; input-output model; agriculture; food industry; elintarvikeala